ISOLASI DAN IDENTIFIKASI SENYAWA AKTIF ANTI BAKTERI PADA DAUN HERBA SISIK NAGA (Drymoglossum piloselloides Presl.) - Surya Cahyadi, Gde Agus; Bawa, I Gusti Agung Gede; Sahara, Emmy (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014, 2014)
This paper discusses the isolation and identification of active compounds from the anti bacterial herb leaf of dragon scales (Drymoglossum piloselloides Presl.). 500 grams of dried leaf powder of dragon scales produced 26.4376 grams of concentrate ethanol extract. Phytochemical test showed that the ethanol extract containing compounds of flavonoid, triterpenoid and polyphenol. The results of the partition of the ethanol extract using n - hexane, chloroform and n - butanol, followed by evaporating yielded 3.8824 g of  concentrate extract of n- hexane, 9.1124 grams of concentrate extract of chloroform and 4.4921 grams of concentrate extract of n-butanol. Anti-bacterial activity assay sugested that the concentrate extract of n - butanol showed the greatest inhibition activity against bacteria of Staphyloccocus aureus , which was of 0.90 cm. The concentrate extract of n - butanol was then separated and purified, and hence 0.2323 grams of anti- bacterial extract was obtained. The result of the phytochemical test showed that the active isolate of herb leaf of dragon scales was flavonoid compound. Identification by UV - Vis spectrophotometry gave two absorption bands in the ultraviolet region. The first band was at the wavelength of 318.00 nm and the second one at the wavelength of 271.50 nm. These results indicated that the active isolates containing electronic transitions of  ? ? ?* of an aromatic compound and  n ? ?* of an aromatic compound as well which are the characteristic of flavonoid compounds.  Identification by infrared spectrophotometry showed that the active isolates containing hydroxyl group (- OH ) which appeared at the wave number of 3512.37 cm - 1 ; o - hydroxy aryl ketones at the wave numbers of 2924.09 cm ??- 1 and 2858.51 cm - 1 with medium intensity and broaden band. It was also observed the presence of benzene trisubstituted (1,2,3 or 1,3,5 - trisubstituted) at the wavelength of 1734.01 cm - 1 with medium intensity and broaden band.
Keywords: isolation, identification, Drymoglossum piloselloides Presl., Staphyloccocus aureus, flavonoids